The diversity of Profil Pelajar Pancasila's concept in English textbook: A linguistic evidence - Purnama Rika Perdana; Putri Oktaviani; Najmi Hillalliyati; Siti Sadiah (English Learning Innovation, 2025)
The study investigates integrating the Profil Pelajar Pancasila values in English textbooks within Indonesia's Merdeka Curriculum framework. The research focuses on diversity, a key element in the Profil Pelajar Pancasila, and how it is reflected in the textbooks designed for primary school students. Using a qualitative approach through a literature review and content analysis of My Next Words English Textbooks for third-grade students, this study evaluates the extent to which the values of global diversity, tolerance, and cultural representation are embedded in the materials. The result of this study found that global diversity is the most frequently found in English textbooks for third-grade students. Global diversity creates a sense of mutual knowledge and appreciation of intercultural communication skills with others and reflects responsibility for diverse experiences. The themes and content in the English textbook align with the purpose of Profil Pelajar Pancasila's students, which is to make students aware of global diversity, respect cultural differences, and be able to interact globally